Botswana : 2011 Article IV Consultation: Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Botswana. (IMF Staff Country Reports; Country Report ;, 2011)
Botswana's economy staged an impressive recovery during the past year. The strong economic recovery has helped stabilize financial market conditions. The overall external position has also strengthened. The overriding economic policy challenges are to reduce the size of government sustaining growth, diversify the economy, and improve its quality. The monetary and fiscal policy stance on the global food and fuel price shocks has been commended by Executive Directors. Sustaining growth, broadening its sources, and improving its quality are key policy priorities of the government.